Feasibility of Implementing Infant Home Visiting in a Central Australian Aboriginal Community - Nguyen, Ha (Prev Sci, 2018)
The Australian Nurse-Family-Partnership Program, an adaption of the Olds’ Nurse-Family-Partnership (NFP), commenced in Alice Springs in 2009 (Central Australia FPP), aiming to improve the health and social outcomes of Aboriginal mothers and infants. This study explores the feasibility of NFP implementation in a remote Australian Aboriginal community. Feasibility was defined by programme uptake by eligible women, retention in the programme, actual vs. scheduled visits and extent of programme content delivery. Programme uptake was established from pregnancy data in the patient Clinical Information System and programme referrals to December 31, 2015. Rates of withdrawal, retention and content delivery were derived from FPP data and compared with published NFP data. Modified Poisson regression was used to identify client characteristics associated with retention beyond the child’s first birthday. There were 469 valid referrals (43% of eligible pregnancies) and 299 women with at least one completed home visit by December 31, 2015. Of these, 41% completed the programme to the child’s second birthday and 53% beyond the child’s first birthday. Dominant reasons for leaving were “moved out of service area” (35%) and “declined further participation” (35%). There was a statistically significant positive association for programme retention with later gestational age at referral (RR = 1.27, p value = 0.03). A high proportion (75%) of scheduled visits was achieved and high delivery of programme content (80%). Central Australia FPP is the first implementation of the NFP model in a remote Aboriginal community. This study found that it can be implemented successfully in this setting. Outcome evaluation is needed to test achievement of hypothesised benefits.